Sedentary behavior is associated with physical activity, functional capacity, and a history of stroke in patients with heart failure. A cross-sectional study - Ila MF Bendassolli; Antonio G Oliveira; Eduardo C Costa; Dyego LB de Souza; Eulália MC Maia (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aims: Sedentary behavior (SB) has emerged as an important risk factor for poor health. Evidence showed that patients with heart failure (HF) exhibit high levels of SB, and that high SB increases mortality among such patients. We aimed to identify factors associated with SB in HF patients. Methods: A cross-sectional study was carried out with adults with HF and categorized under New York Heart Association (NYHA) functional class I-III. Sociodemographic, clinical, and health information were gathered. Evaluation of SB (by sitting time) and moderate-to-vigorous physical activity (MVPA) was performed by self-reported measures. Functional capacity was assessed using the Duke Activity Status Index. Simple and multivariate linear regression analyses were performed to identify the most suitable predictive model. Results: The sample (n = 80) comprised predominantly of patients in functional class I, men, and with an average age of 50.8 years. Time spent on SB totaled to 7.69 ± 2.35 h/day. Weekly volume of MVPA, functional capacity, and previous stroke were predictors of higher SB. Using simple linear regression analysis, the variables body mass index, quality of life, NYHA functional class, total comorbidities, dyslipidemia, MVPA in the leisure domain, and the use of diuretics, statins, and sildenafil were shown to have a statistically significant association with SB. Conclusion: In patients with HF, a longer time spent in SB was associated with low volumes of MVPA, low functional capacity, and history of stroke. More studies are needed to corroborate these findings.